2014
DOI: 10.1364/boe.5.003403
|View full text |Cite
|
Sign up to set email alerts
|

Coherent hemodynamics spectroscopy in a single step

Abstract: Coherent Hemodynamics Spectroscopy (CHS) is a technique based on inducing cerebral hemodynamic oscillations at multiple frequencies, measuring them with near-infrared spectroscopy (NIRS), and analyzing them with a hemodynamic model to obtain physiological information such as blood transit times in the microvasculature and the autoregulation cutoff frequency. We have previously demonstrated that such oscillations can be induced one frequency at a time. Here we demonstrate that CHS can be performed by a single i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…4(A)); this noise assignment, in turn, prompted the need for increased temporal averaging. Interestingly, although heartbeat oscillations are well recognized in the NIRS community [63][64][65], the DCS community has been comparatively slow to appreciate the full potential of fast blood flow measurements.…”
Section: Discussionmentioning
confidence: 99%
“…4(A)); this noise assignment, in turn, prompted the need for increased temporal averaging. Interestingly, although heartbeat oscillations are well recognized in the NIRS community [63][64][65], the DCS community has been comparatively slow to appreciate the full potential of fast blood flow measurements.…”
Section: Discussionmentioning
confidence: 99%
“…22 As shown above for the arterial saturation, if blood flow contributions are negligible, then Arg½D − Arg½O ¼ 0. However, we have previously demonstrated, [13][14][15][16]29 and we will show again here that this is not the case for brain measurements, where blood flow contributions cannot be neglected. Hence, it is not correct to use the ratio jOj∕jTj to obtain S ðvÞ from data collected during paced or normal breathing, since O ≠ O V .…”
Section: Measuring the Venous Saturation From Volumementioning
confidence: 57%
“…We have repeatedly shown that oxy-and deoxyhemoglobin measurements on muscle tissue are in phase 14 at the respiratory frequency, indicating that blood volume changes are dominant and blood flow changes can be considered negligible. However, cerebral measurements have shown a consistent out of phase behavior between oxy-and deoxyhemoglobin, [14][15][16][17][18][19] indicating that blood flow changes are not a negligible contributor to the optical signals. The reason for this is that blood volume changes are smaller in the brain than other tissues due to the rigid enclosure of the skull, 20 damping the magnitude of vessel diameter changes.…”
Section: Arterial Saturation Measurements By Pulsementioning
confidence: 99%
See 1 more Smart Citation
“…The search regions for the fitting parameters are defined by ranges found in the literature. 18 The analytical expressions derived from the hemodynamic model and the simplifying assumptions relating these six hemodynamic parameters and the CHS spectra are described in detail in Kainerstorfer et al 19 In the case of breast measurements, because the phasors Dðω i Þ, Oðω i Þ, and Tðω i Þ were found to be in-phase with each other at all measured frequencies, the amplitude ratio jOðω i Þj∕jTðω i Þj provides a measure of the oxygen saturation of hemoglobin in the volume-oscillating vascular compartments, 9 which we indicate here with S V . This measure of hemoglobin saturation is a weighted average of the saturations of the volume-oscillating compartments, where each vascular compartment is weighted according to its relative contributions to the overall blood volume oscillations:…”
Section: Oðωþmentioning
confidence: 99%